Influence of Rhodiola rosea on the heat acclimation process in young healthy men - Timpmann, Saima; Hackney, Anthony C; Tamm, Maria; Kreegipuu, Kairi; Unt, Eve; Ööpik, Vahur (Applied physiology, nutrition, and metabolism, 2018)
The adaptogen Rhodiola rosea (RR) may mitigate stress responses and have beneficial effects on endurance capacity (EC) and mental performance. Heat acclimation (HA) improves EC in the heat, but the potential impact of RR on the HA process is unknown. Therefore, our intent was to determine if RR has a positive impact on HA. Twenty male subjects (age, 22.5 ± 3.0 years) completed 2 EC tests involving walking (6 km·h −1 ) until volitional exhaustion in a climate chamber (air temperature, 42 °C; relative humidity, 18%) before (H1) and after (H2) an 8-day HA period. One group (SHR; n = 10) ingested standardised extract SHR-5 of RR (a single daily dose of 432 mg), while a second group (PLC; n = 10) administered a placebo prior to each HA session. Efficacy of HA was evaluated on the basis of changes that occurred from H1 to H2 in the time to exhaustion (TTE), exercise heart rate (HR), core and skin temperatures (T c , T sk ), stress hormones, ratings of perceived exertion (RPE) and fatigue (RPF), and thermal sensation (TS). HA significantly increased TTE (133.1 ± 44.1 min in H1; 233.4 ± 59.8 min in H2; p < 0.0001) and decreased (p < 0.0001) HR, T c , T sk , stress hormones as well as RPE, RPF, and TS. However, the magnitude of all these changes was similar (p > 0.05) in the SHR and PLC groups. These results suggest that the use of RR during HA has no beneficial performance, physiological, or perceptual effects in young healthy males.